(untitled) (Research, Society and Development, 2021)
The university environment can trigger a worsening in the well-being of young academics and many university managers are seeking strategies for this problem, such as animal-assisted intervention. The aim of the study was to evaluate the effect of interaction with co-therapist dogs on well-being and physiological parameters such as pulse, systolic and diastolic blood pressure of students from two university courses in Pelotas, RS. Thirty-eight university students from the field of animal health (Veterinary Medicine) and human health (Psychology) participated. An intervention was performed lasting 40 to 50 minutes for each in which the students interacted with four co-therapist dogs based on playful activities. The evaluations occurred before and after the intervention, and subjective well-being was measured through the Andrews Face Scale only of veterinary students and by measuring pulse, systolic and diastolic blood pressure only of psychology students. The results were obtained from the paired Student’s T-test. A significant improvement was observed in the facial expressions of the students when evaluating pre (0.78 ± 1.043) and post-intervention with the co-therapist dogs (2.70 ± 0.635), in addition to significant reductions in the mean values before and after pulse intervention, decreasing from 85.13 to 80.87 bpm (p = 0.025) and also in systolic blood pressure, decreasing from 118.67 to 108.00 bpm (p = 0.010). There was no significant reduction in diastolic blood pressure. These results allowed to conclude that there was a positive effect on the well-being and physiological parameters of the students from a single intervention.